An Analysis of Idiomatic Expressions Found in ‘A Dog’s Journey’ (2019) Movie Script - Herman .; Rohani Nirmana Hasibuan (Research and Community Services Institutes of Udayana University, 2020)
This research is conducted in purpose to identify types of idiomatic expressions found in “A Dog’s Journey” (2019) Movie Script. The researchers used Lim’s theory (2004). The source of data was the script of movie entitled A Dog’s Journey. The methodology which used in this research was qualitative research which specifically referred to document content analysis method. Method of collecting the data was searching the movie, downloading, watching and understanding the whole movie. After collecting the data, the researchers did data preparation, data reading, data confirmation, and calculation as the data analysis. After investigating the types of idiomatic expressions found in A Dog’s Journey (2019) movie, the researchers found 36 idiomatic expressions. The idiomatic expressions in A Dog’s Journey (2019) movie have been analyzed in types; there were 17 phrasal verbs with percentage 47,2%, 3 phrasal prepositional phrase with percentage 8,3%, 3 prepositional phrase with percentage 8,3%, 3 idioms with noun as keywords and with percentage 8,3% , 5 idioms with verb as keywords and with percentage 13,8%, 4 idioms with adjective as keywords and with percentage 11,1% and 1 idiomatic pairs with percentage 2,7%. The conclusion of this research was the dominant of idiomatic expression used in A Dog’s Journey (2019) movie is phrasal verb.